'It makes life so much easier'—experiences of users of the MicroGuide™ smartphone app for improving antibiotic prescribing behaviour in UK hospitals: an interview study. Issue 3 (12th August 2021) - Hand, Kieran S; Clancy, Bridget; Allen, Mike; Mayes, Amazigom; Patel, Yash; Latter, Susan M
Abstract: Objectives: To understand the impact on prescribing behaviour of an antimicrobial therapy guidelines smartphone app, in widespread use in hospitals in the UK. Methods: Twenty-eight doctors and five nurse prescribers from four purposively selected hospitals in the UK participated in behavioural theory-informed semi-structured interviews about their experiences of using the MicroGuide™ smartphone app. Data were analysed using a thematic content analysis. Results: Five themes emerged from the interview data: convenience and accessibility; validation of prescribing decisions; trust in app content; promotion of antimicrobial stewardship; and limitations and concerns. Participants appreciated the perceived convenience, accessibility and timesaving attributes of the app, potentially contributing to more prompt treatment of patients with time-critical illness. The interviewees also reported finding it reassuring to use the app to support decision-making and to validate existing knowledge. They trusted the app content authored by local experts and considered it to be evidence-based and up-to-date. This was believed to result in fewer telephone calls to the microbiology department for advice. Participants recognized the value of the app for supporting the goals of antimicrobial stewardship by promoting the responsible and proportionate use of antimicrobials. Finally, a number of limitations of the app were reported, including the risk of de-skilling trainees, cultural problems with using smartphones in clinical environments and software technical problems. Conclusions: The MicroGuide app was valued as a means of addressing an unmet need for updated, concise, trustworthy specialist information in an accessible format at the bedside to support safe and effective antimicrobial prescribing.